Multiple Faces of Conventional Political Activism: A Youth Council Case Study - Pirk, Reelika; Nugin, Raili (Studies of Transition States and Societies, 2016)
Youth political participation via state-sponsored institutional settlements has always been considered a goal of youth policies, representing a means of creating politically active and caring citizens. Throughout Europe, however, the number of politically active young people seems to be diminishing, with youth frequently described as apathetic and disengaged. While a growing body of academic research has concentrated on exploring the reasons behind political inactivity, this article explores the motivation and activities of some of the young people who are involved in institutionalised youth organisations, asking if the meanings behind institutional political participation are undergoing a process of change together with the rest of the society. Based on qualitative in-depth interviews, participant observation and analysis of documents (including online communication) collected as part of the research project MYPLACE, we examine the meanings young people attach to their participation. We show that the character of these organisations and motivations behind participation are miscellaneous; sometimes strikingly similar to the forms of participation not traditionally associated with political activism but rather ascribed to disengaged youth.